Flushing sand-laden manure - Joseph P. Harner; T.D. Strahm; James P. Murphy (Kansas Agricultural Experiment Station Research Reports, 2000)
Sand can be handled successfully either in a scrape or flush system by developing handling systems that allow for the sand-laden manure to settle prior to the effluent entering a lagoon. The abrasiveness and density of sand create problems in handling the manure. Manure weighs about 60 lb/cu ft, whereas sand has a density of 120 lb/cu ft. Sand-laden manure will have an approximate density of 80 lb/cu ft, if 30% of the manure is sand. Because sand is heavier, it will not remain in suspension as long as manure and settles rapidly. Many problems associated with handling sand-laden manure can be avoided if the solids are stored separately from the effluent.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Flush; Sand; Manure; Bedding